The legal effect of electronic bonds lacking an authenticated signature in Jordanian legislation - Ahmad Albnian; Ali Al-Hammouri; Tareq Al-Billeh; Mohammed Al Makhmari; Roua Belghit; Mohammed Chakib Himmich (Jurnal Hukum Novelty, 2025)
Introduction to the Problem: This study examines the Jordanian legislator's stance on the conditions for electronic signatures, as outlined in the Electronic Transactions Law and the Jordanian Evidence Law. It aims to assess the consistency between the two laws, particularly since the Electronic Transactions Law specifies requirements for electronic signatures, while the Evidence Law remains silent on such conditions. Purpose/Objective Study: This study aims to examine how the recognition and enforceability of electronic bonds vary depending on the type of electronic signature used—specifically comparing authenticated and secured signatures versus unauthenticated yet secured signatures. The analysis will assess the impact of these signatures on the validity and legal standing of electronic bonds, similar to how handwritten signatures affect traditional bonds. Identifying gaps in this relationship will help address potential shortcomings in ensuring authenticity and legal compliance. Design/Methodology/Approach: In this study, we follow two approaches: the descriptive approach in presenting electronic bonds, their types, protection, the validity of an authenticated and protected electronic signature in one hand, and the unauthenticated and unprotected electronic signature. The analytical approach was also relied on. The legal texts regulating the process of electronic bonds and electronic signatures will be reviewed, analyzed, and compared with other laws. Findings: The study highlights how electronic authentication can streamline international trade by reducing documentation costs, provided legal frameworks ensure security and reliability. While Jordan’s Electronic Transactions Law grants e-signatures legal validity, gaps remain in regulating authentication entities. Key recommendations include: (1) establishing an 'electronic examiner' to verify signatures, (2) clarifying certification providers’ liability for data protection, and (3) formalizing government-contractor agreements for authentication services. Strengthening judicial training on digital transactions is also advised to enhance enforcement. Paper Type: Research Article